Language choice and use of English and Persian among Iranian postgraduate students in a Malaysian public university - Maryamabadi, Narjes Karimi (2014)
The purpose of this study is to find out the attitudes of Iranian postgraduate students studying in UPM towards English and Persian language and, also to identify thei r language use and choice patterns in different domains. These domains include family, education,environment, media; reading and writing; each of these domains have 3 or 4 sub domains. The relationship between gender and language attitude and language choice is also examined as well as the relation between study discipline (science and social science) and language attitude and language choice. The study uses Fishman’s (1972), “who speaks what language and to whom”, model of domain analysis to determine their language choice and use. Using self-administered questionnaires the data was gathered. The questionnaire was adopted from previous studies, but some changes were made to suit the objectives of this study. Questionnaires were distributed to a sample of 170 posts graduate students from different faculties of UPM. One hundred and fifty-one (151) questionnaires were returned. Using SPSS, the data was analyzed. Statistical procedures of analysis were used in accordance to their relevance with the current study’s objectives. To provide descriptive information frequency analysis was used. Other techniques were t-test and Pearson correlation to find the difference and correlation between variables. Results of this study indicate that language choice and use is domain specific. They use ifferent languages in different domains. In the family domain, Persian is almost the onlylanguage they use, as family is an intimate domain. In formal domains such as education, English is the language which is used in most of the situations as medium of the instruction in the University is English. As for the media domain, writing and reading domains students use English and Persian in different situations. The relationships of language choice, attitude, and gender and study discipline were alsoexamined. In general, no significant difference was found between male and female in language choice and use. But male and female played out a significant difference in their attitude towards the English language. The effect study discipline on language choice showed some choice difference between students studying science and social science fields.